ЗОНИ ЕФЕКТИВНОГО РЕГУЛЮВАННЯ НАПРУГИ ДЖЕРЕЛАМИ РОЗОСЕРЕДЖЕНОЇ ГЕНЕРАЦІЇ З ІНВЕРТОРНИМ ПРИЄДНАННЯМ У РОЗПОДІЛЬНІЙ ЕЛЕКТРИЧНІЙ МЕРЕЖІ - Труніна, Г.О. (Інститут електродинаміки НАН України, Київ, 2014)
An approach for the determination of areas of effective voltage control by distributed generation with inverter interconnection in distribution networks based on the calculation and analysis of the sensitivity of the voltage at the nodes of the system to a change in the generation of active and reactive power at the connection of distributed generation. This study allows to determine in which areas of the network voltage regulation due to distributed generation will have the greatest effect, and which nodes need additional means for voltage regulation . References 4, figures 3.